2015
DOI: 10.1016/j.ijheh.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Urinary triclosan concentrations are inversely associated with body mass index and waist circumference in the US general population: Experience in NHANES 2003–2010

Abstract: Background Humans are extensively exposed to triclosan, an antibacterial and antifungal agent. Triclosan’s effects on human health, however, have not been carefully investigated. Objective To examine whether triclosan exposure is associated with obesity traits. Methods This study included 2,898 children (6-19 years old) and 5,066 adults (20 years or older) who participated in the National Health and Nutrition Examination Surveys (NHANES) 2003-2010 and had a detectable level of urinary triclosan. Multiple l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 39 publications
4
45
0
Order By: Relevance
“…Cross-sectional studies have reported relationships between 2,5-dichlorophenol and triclosan with body size outcomes (Buser and others 2014; Lankester and others 2013; Li and others 2015; Wei and others 2014). However, cross-sectional studies that measure concurrent exposures and outcomes cannot establish causality (Engel and Wolff 2013) and it is possible that exposures to these chemicals or their precurcors may be influenced by factors associated with body size, rather than vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies have reported relationships between 2,5-dichlorophenol and triclosan with body size outcomes (Buser and others 2014; Lankester and others 2013; Li and others 2015; Wei and others 2014). However, cross-sectional studies that measure concurrent exposures and outcomes cannot establish causality (Engel and Wolff 2013) and it is possible that exposures to these chemicals or their precurcors may be influenced by factors associated with body size, rather than vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Most analyses yielded findings consistent with the null hypothesis. In two NHANES studies that observed significant associations (Lankester et al 2013;Li et al 2015), the results were in opposite directions.…”
Section: Measures Of Overweight and Obesitymentioning
confidence: 90%
“…Of the 43 studies, 24 were conducted in North America (Wolff et al , 2010(Wolff et al , 2015Clayton et al 2011;You et al 2011;Buttke et al 2012;Savage et al 2012Savage et al , 2014Koeppe et al 2013;Lankester et al 2013;Buser et al 2014;Spanier et al 2014;Adgent and Rogan 2015;Li et al 2015;Ihde et al 2015;Shiue 2015aShiue , 2015bVelez et al 2015;Ashley-Martin et al 2016;Buckley et al 2016;Poole et al 2016;Scinicariello and Buser 2016;Smarr et al 2017;Geer et al 2017), two studies in the Caribbean (Watkins et al 2015;Aker et al 2016), 10 studies in Europe (Allmyr et al 2009;Chevrier et al 2012;Philippat et al 2012Philippat et al , 2014Bertelsen et al 2013;Buhl et al 2014;Den Hond et al 2013, 2015Geens et al 2015;Lassen et al 2016), four in Asia (Chen et al 2013;Wang et al 2015;Xue et al 2015;Zhu et al 2016), and three in Australia (Cullinan et al 2012(Cullinan et al , 2015a…”
Section: Overview Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…152,153 Two cross-sectional studies using 6–19 year old children from the National Health and Nutrition Examination Survey report conflicting results. One publication (years: 2007–2010), found no association between urinary triclosan concentrations and BMI z-score, waist circumference, or prevalence of being overweight or obese.…”
Section: Triclosanmentioning
confidence: 99%